Effect of Clitoria ternatea on PCOS - Molecular Docking Study (International Journal of Food and Nutritional Sciences, 2022)
Polycystic Ovarian Syndrome is a heterogeneous disorder. It is the most common endocrinopathy inwomen and the most common cause of anovulatory infertility. Hyperandrogenism is a salient featureof PCOS. At present, Hormone therapy and chemical drugs are recommended for the treatment ofhyperandrogenism in PCOS and this treatment has several adverse side effects. Hence Traditionalmedicine remedies have become an emerging trend among people without any side effects. In traditionaland modern medicine, Clitoria ternatea is focused on as an enhancer of reproductive health. The presentstudy was undertaken to develop a Nutraceutical product - capsule filled with powdered dry Clitoriaternatea flower for the treatment of PCOS. The formulated Nutraceutical product (capsule) was rich inminerals and total flavonoids. It contained 93.4% of moisture, 6% of total ash, 445.8 mg/100 g ofcalcium, 811.2 mg/100 g of potassium, 143.5 mg/100 g of magnesium, and 102 mg QE/g of totalflavonoids. The binding affinity of flavonoids such as Quercetin, Kaempferol, and Myricetin as presentin the petals of Clitoria ternatea were explored with the protein CYP 17-cytochrome P450 which isresponsible for hyperandrogenism due to its overexpression and leads to PCOS. The binding affinityof Ketoconazole, Spironolactone, and Flutamide (which are all used as drugs for treatinghyperandrogenism) were also explored with the protein CYP 17-cytochrome P450 to compare theefficiency of flavonoids in the treatment of PCOS.